The Impact of Cholera on the Design and Implementation of Toronto's First Municipal By-laws, 1834 - Atkinson, Logan (Urban History Review / Revue d'histoire urbaine, 2002)
The City of Toronto was incorporated in 1834 amid much political animosity and turmoil. The tension between the executive administration and its tory sympathizers on the one hand, and the promoters of reform on the other, had moved political matters to a critical juncture. Perhaps inconsistent with this struggle between central and municipal authority in Upper Canada was the statute by which the City was created, a statute that settled virtually complete legislative authority on the local government. But the first municipal election returned a reform majority to Toronto's council, with the intransigent William Lyon Mackenzie as first mayor, further heightening the difficulties between the central authority and the local administration.It might be anticipated that, when the City turned its attention to passing its first set of by-laws in the late spring of 1834, the contest over the right organization of government would dominate the thinking of City councillors. However, a review of those by-laws and the issues that gave rise to them reveals that environmental concerns, including the threat of a repeat of the dangerous cholera epidemic of 1832, had as much to do with the ultimate design of those by-laws as did political orientation. In fact, the environmental pressures felt at the time allowed for the transcendence of political differences for the sake of the defence of public health, a result quite inconsistent with dominant interpretations of the role of law and legal institutions in the Upper Canadian experience.